Canon and criterion in Christian theology : from the Fathers to feminism - Abraham, William J. (William James), 1947-2021 (Clarendon Press ; Oxford University Press, 1998)
This is a study of canon in the Christian tradition. Standard accounts locate the canonical heritage of the church within epistemology. The author explores the consquences of this move, from the Fathers to modern feminist theology.